Evaluation of the prognostic value of cellular inhibitor of apoptosis protein in epithelial ovarian cancer using automated quantitative protein analysis - Psyrri, A.; Yu, Z.; Bamias, A.; Weinberger, P.M.; Markakis, S.; Kowalski, D.; Camp, R.L.; Rimm, D.L.; Dimopoulos, M.A. (Cancer Epidemiology Biomarkers and Prevention, 2006)
Purpose: The cellular inhibitor of apoptosis protein (cIAP) is regarded as an important prognostic biomarker in cancer. Here, we sought to determine the prognostic value of cIAP protein levels in epithelial ovarian cancer using a novel method of compartmentalized in situ protein analysis. Methods: A tissue array composed of 150 advanced-stage ovarian cancers, treated with surgical debulking followed by platinum/paclitaxel-based combination chemotherapy, was constructed. For evaluation of protein expression, we used an immunofluorescence-based method of automated in situ quantitative measurement of protein analysis. Results: The mean follow-up time for the entire cohort was 34.4 months. Patients with tumors bearing high cIAP membranous expression had a 3-year survival rate of 31% compared with 73% for patients with low cIAP expressing tumors (P = 0.0020). In multivariable analysis, adjusting for well-characterized prognostic variables, low membranous cIAP expression level was the only significant prognostic factor for overall survival. Conclusions: Our results indicate that cIAP protein levels have prognostic value in ovarian cancer patients. Modulation of cIAP levels may improve clinical outcome in ovarian cancer. Copyright © 2006 American Association for Cancer Research.